Cultural Commentary: Staring Back and Forth: The Photographs of Kevin Connolly - Millett, Ann (Disability Studies Quarterly, 2008)
Kevin Connolly, who was born without legs, photographs people staring at him around the world. The photographs represent staring as a multi-cultural and multi-generation act. In this paper, I discuss the phenomena of staring in art and everyday life, from perspectives of art history and disability studies, in relationship to Connolly's photographs. I argue that Connelly's photographs reveal an embodied perspective and subject position of disability through staring back.